2022
DOI: 10.3390/ijms23073613
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Formation of Size-Selected Clusters upon Pickup of Dopants into Multiply Charged Helium Droplets

Abstract: Properties of clusters often depend critically on the exact number of atomic or molecular building blocks, however, most methods of cluster formation lead to a broad, size distribution and cluster intensity anomalies that are often designated as magic numbers. Here we present a novel approach of breeding size-selected clusters via pickup of dopants into multiply charged helium nanodroplets. The size and charge state of the initially undoped droplets and the vapor pressure of the dopant in the pickup region, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…A significant complication in the atomistic modeling of these systems arises from their large size that makes the use of a polarizable model challenging. The ion emission mechanism and the ion dopant distributions from multicharged supercooled helium droplets add even more interesting questions to be examined related to the role of a low dielectric constant solvent in the released cluster ion distributions. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant complication in the atomistic modeling of these systems arises from their large size that makes the use of a polarizable model challenging. The ion emission mechanism and the ion dopant distributions from multicharged supercooled helium droplets add even more interesting questions to be examined related to the role of a low dielectric constant solvent in the released cluster ion distributions. , …”
Section: Discussionmentioning
confidence: 99%
“…The ion emission mechanism and the ion dopant distributions from multicharged supercooled helium droplets add even more interesting questions to be examined related to the role of a low dielectric constant solvent in the released cluster ion distributions. 32,69 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion-emission mechanism and the ion-dopant distributions from multi-charged supercooled helium droplets add even more interesting questions to be examined related to the role of a low dielectric constant solvent in the released cluster-ion distributions. 32,69 Supporting Information…”
Section: Discussionmentioning
confidence: 99%
“…8,9,26,27 The process can be written as Since IEM is considered to take place in nanodroplets with a radius of approximately 10 nm its direct experimental detection has been challenging and as a result there are continuous efforts for its verification. 8,[30][31][32] In a recent article, 31 Williams et al observed ion-emission from electrosprayed droplets with mass ranging from 1-10 MDa (which corresponds to 55000 to 550000 water molecules) at charge state of ≈ +50-300e (where e denotes the positive elementary charge). The mean charge loss at an emission event is 1.1e, which implies that the majority of the emission events corresponds to the loss of a single charge, with rare occurrence of a loss of double or triple charge.…”
Section: Introductionmentioning
confidence: 99%